Abuse, Exploitation and Discrimination: The Stark Reality (A Policy and Action Research on Filipino Female Children in Specially Difficult Circumstances) - Sobritchea, Carolyn I.; Mondiguing, Remedios P.; Ortega, Susan (Review of Women's Studies; Vol 11 No 1-2 (2001): Review of Women's Studies Volume XI, Numbers 1-2 (January-December 2001))
---